Functional titanium refined stemming for in-situ synthesized blast furnace

By using in-situ synthesis technology in blast furnace titanium fine gun mud, TiN and Ti(C,N) solid solutions are generated, and the shortcomings of existing titanium-containing gun mud in formula, plasticity and fire resistance are solved, and the effect of efficient protection and prolonging the service life of blast furnace is achieved.

CN119683976APending Publication Date: 2025-03-25YIXING REFRACTORY EQUIP & MATERIAL FACTORY

Patent Information

Application Number
CN202411810658.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing titanium-containing cannon mud for blast furnaces has shortcomings in formula, plasticity, raw material purity and fire resistance, resulting in difficulty in maintaining the iron port of blast furnace and short service life.

Method used

In situ synthesized functional titanium fine gun mud for blast furnaces is used to generate TiC, TiN and Ti(C,N) solid solutions by mixing specific proportional components such as the first bauxite, the second bauxite, silicon carbide, cyanite, ferrosilicon nitride, Guangxi mud, titanium-containing raw materials, carbon sources, catalysts, metal silicon powder and nitrogen sources to improve the performance of gun mud.

Benefits of technology

It extends the iron discharge time and iron port depth of the blast furnace, forms a protective layer to reduce the furnace wall temperature, improves the protection and repair capabilities of the iron port, and extends the service life of the blast furnace. At the same time, it is simple in process, low production cost, and environmentally friendly and pollution-free.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683976A_ABST
    Figure CN119683976A_ABST
Patent Text Reader

Abstract

The invention discloses in-situ synthesized functional titanium fine stemming for a blast furnace, and belongs to the field of metallurgy. The high-strength and high-toughness refractory material is prepared from the following components in parts by weight: 8-15 parts of first alumina, 8-15 parts of second alumina, 8-15 parts of first silicon carbide, 7-15 parts of kyanite with the particle size of 1-0 mm, 8-15 parts of ferro-silicon nitride, 10-20 parts of second silicon carbide, 3-8 parts of Guangxi mud, 5-15 parts of a titanium-containing raw material, 1-3 parts of a carbon source, 1-3 parts of a catalyst, 1-3 parts of metal silicon powder, 1-7 parts of a nitrogen source and 10 parts of a binding agent. The stemming has the characteristics of simple and convenient process, low production cost, environmental protection and no pollution, the performance of the stemming is stable due to the self-generated TiC, TiN and Ti (C, N) solid solutions, and the stemming shows excellent low-temperature and medium-temperature strength, high volume density, low sintering shrinkage rate and good slag iron corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgy, and in particular relates to an in-situ synthesized functional titanium fine taphole mud for blast furnace. Background Art

[0002] With the continuous development of blast furnace technology, modern blast furnaces are gradually moving towards large-scale, high wind pressure, and low iron-tapping frequency, which puts higher requirements on the performance of anhydrous taphole mud. As a functional refractory material for plugging the taphole of a blast furnace, taphole mud not only needs to have good plasticity for easy construction operation, but also must have excellent resistance to slag iron erosion and scouring. In addition, in order to maintain the stability of the taphole, taphole mud must also have strong anti-erosion performance and form a stable mud bag in the taphole to protect the surrounding lining bricks.

[0003] In the production process of blast furnace, the erosion of the hearth has always been the biggest safety hazard. The iron mouth is often washed and eroded by high-temperature slag, which makes the iron mouth a weak link in the blast furnace. Therefore, the maintenance of the iron mouth has become a key task in blast furnace production, which is directly related to the normal operation and service life of the blast furnace. Since the early 1980s, my country's blast furnaces have begun to apply titanium-containing material furnace protection technology. After decades of development, this technology has been widely used.

[0004] At present, there are mainly the following methods for adding titanium-containing materials into the furnace: first, directly adding titanium-containing materials to the blast furnace batching; second, adding titanium-containing materials to the sintering batching and entering the furnace with the sintered ore; third, spraying titanium-containing concentrate powder from the tuyere; fourth, when special protection is required near the iron mouth, the titanium-containing materials can be added to the taphole mud. In recent years, the application of titanium-containing taphole mud has become increasingly widespread. However, the existing titanium-containing taphole mud still has many shortcomings in terms of formula, plasticity, raw material purity and refractory properties. Common problems include unreasonable formula, poor plasticity, serious hole expansion, large mud consumption, and difficult iron mouth maintenance. For example, Chinese patent CN1025157789A discloses a blast furnace taphole mud for iron mouth repair and protection. Although the invention optimizes the furnace front operation by using low-cost vanadium-titanium iron powder, due to the low vanadium-titanium content in the vanadium-titanium iron powder, its furnace protection effect and iron mouth repair ability are limited. In addition, when the iron content is too high, the high-temperature strength of the taphole mud will also be seriously affected.

[0005] Based on this, it is of great practical significance to develop a titanium-refined cannon mud with good plasticity, excellent performance, safety and environmental protection, and the ability to quickly generate titanium-containing solid solution in the blast furnace to improve the protection and repair ability of the blast furnace iron mouth and extend the service life of the blast furnace. Summary of the invention

[0006] The first purpose of the present invention is to provide an in-situ synthesized functional titanium cannon mud for blast furnaces. During use, the titanium cannon mud can extend the iron-tapping time and the iron mouth depth of the blast furnace, and can also form a protective layer on the furnace bottom, reduce the furnace wall temperature, and play a role in protecting the furnace cylinder and the furnace bottom.

[0007] The second purpose of the present invention is to provide a method for preparing the above-mentioned functional titanium cannon mud for blast furnace, which has simple steps, low production cost, and is environmentally friendly and pollution-free.

[0008] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0009] The invention discloses an in-situ synthesized functional titanium fine cannon mud for blast furnace. The proportions of each component are as follows, by weight: 8-15 parts of first bauxite, 8-15 parts of second bauxite, 8-15 parts of first silicon carbide, 7-15 parts of 1-0 mm kyanite, 8-15 parts of ferrosilicon nitride, 10-20 parts of second silicon carbide, 3-8 parts of Guangxi mud, 5-15 parts of titanium-containing raw materials, 1-3 parts of carbon sources, 1-3 parts of catalysts, 1-3 parts of metallic silicon powder, 1-7 parts of nitrogen sources and 10 parts of binders.

[0010] Furthermore, the functional titanium fine gun mud for blast furnace is calculated by weight, and the proportions of each component are as follows: 10 parts of the first bauxite, 15 parts of the second bauxite, 10 parts of the first silicon carbide, 10 parts of 1-0mm kyanite, 10 parts of ferrosilicon nitride, 10 parts of the second silicon carbide, 5 parts of Guangxi mud, 10 parts of titanium-containing raw materials, 2 parts of carbon sources, 1 part of catalyst, 2 parts of metallic silicon powder, 5 parts of nitrogen sources and 10 parts of binder.

[0011] Furthermore, the ferrosilicon nitride is 200 mesh ferrosilicon nitride; and the second silicon carbide is 325 mesh silicon carbide.

[0012] Furthermore, the Guangxi mud is 200 mesh Guangxi mud.

[0013] Furthermore, the titanium-containing raw material is 200-mesh high-titanium slag.

[0014] Furthermore, the physical phase of the 200-mesh high-titanium slag is Ti3O5, and the titanium oxide content is ≥80%.

[0015] Furthermore, the carbon source is carbon black with fixed carbon ≥98%, ash ≤16%, S ≤1.0%, moisture ≤1.0% and a particle size of 325 meshes.

[0016] Furthermore, the catalyst is 325 mesh aluminum powder.

[0017] Furthermore, the nitrogen source is selected from one of 200 mesh ammonium sulfate or 200 mesh ammonium dichromate.

[0018] Furthermore, the preparation method of the functional titanium taphole mud for blast furnace described above comprises the following steps:

[0019] Step 1: According to the proportion, ferrosilicon nitride, first silicon carbide, Guangxi mud, high titanium slag, carbon black, metal aluminum powder, metal silicon powder, ammonium sulfate or ammonium dichromate are uniformly premixed in a premixing tank for 30 minutes and set aside;

[0020] Step 2: Add alumina, second silicon carbide, kyanite and part of the binder into a mixer at 70-80°C according to the proportion, and mix for 5 minutes; then, add the fine powder premixed in step 1 into the mixer, and mix for another 5 minutes; then, add the remaining binder, and continue mixing for 50 minutes until it is evenly mixed, and press the mixture into shape to obtain titanium cannon mud.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1) The present invention discloses a new type of titanium cannon clay, which has the characteristics of simple process, low production cost, environmental protection and no pollution. Its spontaneously generated TiC, TiN and Ti(C,N) solid solution make its performance stable, showing excellent low-temperature and medium-temperature strength, high bulk density, low sintering shrinkage and good resistance to slag iron corrosion.

[0023] 2) During the use of the titanium tapping mud of the present invention, the tapping time and the tapping depth of the blast furnace are significantly prolonged, and a protective layer can be formed at the bottom of the furnace to reduce the temperature of the furnace wall and protect the furnace cylinder and the bottom of the furnace.

[0024] 3) The titanium cannon mud prepared by the present invention uses high-titanium slag, carbon black, ammonium sulfate or ammonium dichromate, metal aluminum and other raw materials, which are mixed according to different weight ratios to finally form an in-situ synthesized titanium cannon mud. High-titanium slag is used as the main titanium-containing raw material, with a particle size of 200 mesh, the main phase is Ti3O5, and the titanium oxide content is ≥80%. Carbon black is used as a reducing agent, ammonium sulfate or ammonium dichromate provides nitrogen, and metal aluminum is used as a catalyst to promote the formation of TiC, TiN and Ti(C,N), thereby improving the high temperature resistance and corrosion resistance of the cannon mud. In the blast furnace environment, these titanium compounds can be suspended at the slag-iron interface and deposited at the iron mouth and the furnace bottom brick seams due to their small wetting angles with molten iron and slag, forming a titanium layer with high hardness and excellent heat resistance, effectively protecting the furnace hearth and furnace bottom brick lining, delaying erosion, and thus extending the service life of the blast furnace.

[0025] 4) The present invention uses carbon black as a carbon source, and with its large specific surface area and low thermal expansion coefficient, it promotes the reduction reaction of high-titanium slag and carbon black to generate TiC. At the same time, the uniform dispersion of carbon black enhances the integrity and corrosion resistance of the cannon mud, ensuring its stability in the blast furnace. The nitrogen released by the decomposition of ammonium sulfate or ammonium dichromate at high temperature reacts with the high-titanium slag to generate TiN, which enhances the high-temperature resistance of the cannon mud, and reduces wear through its hardness and wear resistance, further extending the service life of the blast furnace. Metal aluminum acts as a catalyst to reduce the activation energy of the reaction and accelerate the generation of TiC, TiN and Ti(C,N). At the same time, the hydrogen generated by the reaction of metal aluminum with water vapor improves the reduction efficiency of the high-titanium slag, and forms a microporous structure in the iron mouth channel, slowing down the generation of cracks and enhancing the stability and durability of the iron mouth.

[0026] 5) The test results of the titanium tapping mud according to the present invention in the No. 8 large blast furnace of the steel plant showed that after using the titanium tapping mud, the iron mouth depth exceeded 3.8 meters, the iron tapping time exceeded 130 minutes, the mud volume and drill bit consumption were normal, and the iron tapping process was stable; the iron mouth side wall temperature gradually decreased from 318°C to 110°C, proving that it effectively reduced the side wall temperature of the blast furnace and enhanced the protection effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the XRD diffraction pattern of the high titanium slag of the present invention. DETAILED DESCRIPTION

[0028] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0029] In the following examples, ammonium sulfate or ammonium dichromate is used as a substance providing a self-reactive nitrogen source.

[0030] The titanium-containing raw material in titanium fine gun mud is high titanium slag, with a particle size of 200 mesh, a phase of Ti3O5, and a titanium oxide content of ≥80%; the XRD diffraction pattern of high titanium slag is as follows Figure 1 shown.

[0031] The reducing agent is carbon black, with fixed carbon ≥ 98%, ash ≤ 16%, S ≤ 1.0%, and moisture ≤ 1.0%. Its particle size is 325 mesh.

[0032] Metal aluminum is used as a catalyst, and its particle size is 325 mesh.

[0033] The first bauxite is 3-1 mm bauxite, purchased from Yima Ruisen New Materials Co., Ltd.;

[0034] The second bauxite is 1-0 mm bauxite, purchased from Yima Ruisen New Materials Co., Ltd.;

[0035] The first silicon carbide is 3-1mm silicon carbide, purchased from Lanzhou Heqiao Mineral Resources Co., Ltd.;

[0036] The second silicon carbide is 325 mesh silicon carbide, which was purchased from Lanzhou Heqiao Mineral Resources Co., Ltd.

[0037] Examples 1 to 10

[0038] An in-situ synthesized functional titanium fine taphole mud for blast furnace, the components and amounts of which are shown in Table 1 below, calculated by weight.

[0039] Table 1 Comparison of components and dosage of titanium cannon mud in Examples 1 to 10

[0040]

[0041]

[0042] The nitrogen source used in the above embodiments is 200-mesh ammonium sulfate or ammonium dichromate, wherein the nitrogen source used in embodiments 1 to 5 is 200-mesh ammonium sulfate; and the nitrogen source used in embodiments 6 to 10 is 200-mesh ammonium dichromate.

[0043] The preparation method of titanium fine taphole mud in the above-mentioned embodiments 1 to 10 is as follows:

[0044] (1) According to the proportion, the fine powder (including 200 mesh ferrosilicon nitride, first silicon carbide, Guangxi mud, high titanium slag, carbon black, metal aluminum powder, metal silicon powder, ammonium sulfate or ammonium dichromate) is uniformly premixed in a premixing tank for 30 minutes and set aside;

[0045] (2) Add aggregate (alumina, second silicon carbide, kyanite) and half of the binder in proportion to a mixer at 70-80°C and mix for 5 minutes; then, add the fine powder premixed in step (1) to the mixer and mix for another 5 minutes; then, add the remaining half of the binder and continue mixing for 50 minutes until the mixture is uniformly mixed, and press the mixture into a shape to obtain titanium cannon mud.

[0046] During the mixing and grinding process, keep the heating state and control the temperature of the added binder between 70-80℃ to ensure the smooth progress of the mixing process.

[0047] Comparative Example 1

[0048] A conventional taphole clay, calculated by weight, has its components and amounts as shown in Table 2 below.

[0049] Table 2 Components and dosage of titanium fine taphole mud for blast furnace disclosed in Comparative Example 1

[0050] Components Weight 3-1mm alumina 10 servings 3-1mm Silicon Carbide 10 servings 1-0mm alumina 15 servings 1-0mm Kyanite 10 servings 200 mesh Ferro Silicon Nitride 15 servings 325 mesh silicon carbide 20 servings 200 mesh Guangxi mud 5 servings 200 mesh carbon black 2 servings Aluminum powder 1 serving Metal Silicon Powder 2 powder Binder 10 servings

[0051] The preparation method of the above conventional taphole clay is the same as that of Examples 1 to 10.

[0052] The titanium cannon mud for self-reactive blast furnace prepared by the present invention was pressed into a 160mm×40mm×40mm long strip sample at a molding pressure of 10MPa, and then cured at 450℃ for 5h and subjected to carbon embedding heat treatment at 1100℃ and 1500℃ for 3h. The bulk density of the sample was 2.13-2.30g / cm at different temperatures. 3 2.07~2.28g / cm 3 and 2.02~2.20g / cm 3 The room temperature compressive strength is 8~20MPa, 10~25MPa and 13~30MPa respectively; after carbon burial heat treatment at 1500℃×3h, the permanent change rate of the sample is 0.15%~0.30%.

[0053] The titanium taphole mud prepared in each embodiment of the present invention was compared with the conventional taphole mud product in Comparative Example 1 in a large blast furnace in China. Except for the different types of taphole mud, all other reaction conditions were the same. The use results are shown in Table 3 below:

[0054] Table 3 is a comparison of the use effects of titanium taphole mud and conventional taphole mud products in a large blast furnace in China in various embodiments of the present invention.

[0055]

[0056] The test results show that the taphole depth of titanium tapping mud in Example 2 exceeds 3.8 meters, the tapping time exceeds 130 minutes, and the tapping amount and the consumption of the opening drill bit are both within the normal range. During the test, there are fewer phenomena of taphole iron leakage and taphole difficulty, the tapping process is smooth and splash-free, and the iron flow rate remains stable.

[0057] According to the data in Table 3, the titanium taphole mud of Example 2 and the conventional taphole mud of Comparative Example 1 were selected to test the No. 8 taphole and No. 7 taphole of a large blast furnace in a steel plant, with a total test amount of 60 tons. Before use, after 10 days of use, after 20 days of use, and after 30 days of use, the thermocouple was inserted at a depth of 40 cm to test the taphole side wall temperature. The data are shown in Table 4 below.

[0058] Table 4 Comparison of the iron mouth side wall temperature of titanium taphole mud and conventional taphole mud products in Example 2 of the present invention after use in a large domestic blast furnace

[0059] Side wall temperature No. 1 No. 2 Type of taphole clay used Ordinary cannon clay Titanium gun mud Temperature before use 304 318 After 10 days of use 305 216 After 20 days of use 300 156 After 30 days of use 301 113

[0060] According to the analysis of the results, before the use of titanium cannon clay, the side wall temperature at about 1 meter on the right side of the blast furnace iron mouth was 318°C (thermocouple insertion depth 40cm); after the use of titanium cannon clay, the side wall temperature decreased. Although the initial decrease was not large, after 15 days of use, the side wall temperature dropped to below 200°C (196°C), and after 10 days of continued use, the side wall temperature further dropped to about 110°C. Therefore, the use of titanium cannon clay prepared by the present invention can effectively reduce the temperature of the blast furnace side wall, thereby playing a good protective role on the blast furnace side wall.

[0061] In the present invention, by adding ammonium sulfate or ammonium dichromate to the components of titanium fine taphole mud, a series of complex thermal decomposition reactions can occur under the high temperature environment of the taphole mud entering the blast furnace, and nitrogen and other substances are finally generated. The main chemical reaction equation of the process is:

[0062] 3(NH4)2SO4→3SO2↑+4NH3↑+N2↑+6H2O↑

[0063] (NH4)2Cr2O7=N2↑+Cr2O3+4H2O↑

[0064] In this process, the thermal decomposition of ammonium sulfate or ammonium dichromate releases a large amount of nitrogen, which not only helps to maintain the pressure balance in the blast furnace, but also promotes further reaction between the iron mouth channel and the furnace wall of the blast furnace and the high-titanium slag in the taphole. In the high temperature environment of the blast furnace, nitrogen reacts with the high-titanium slag (mainly Ti3O5) in the taphole to generate titanium nitride (TiN). This reaction is very ideal at high temperatures. The generated TiN has excellent refractory, high hardness and wear resistance, which can reduce the wear of blast furnace materials and thus extend the service life of the blast furnace. For the operation of blast furnaces in the steel industry, it has significant economic benefits and technical value.

[0065] according to Figure 1 As shown, in the present invention, high titanium slag is used as the titanium-containing raw material, and its phase is mainly Ti3O5. The reduction process of titanium oxide in the blast furnace follows the following reaction path:

[0066] TiO2→Ti3O5→Ti2O3→TiO→Ti→Ti(C,N)

[0067] When titanium oxide-containing titanium fine gun mud enters the blast furnace, titanium oxide is gradually reduced, and titanium oxide reacts with carbon to form TiC, TiN or Ti(C,N) solid solution. The main reaction equation is as follows:

[0068] (TiO2)+3C=TiC+2CO

[0069] (TiO2)+2C+1 / 2N2=TiN+2CO

[0070] (TiO2)+3[C]=TiC+2CO

[0071] TiC, TiN or Ti(C,N) will be enriched and grow during the sedimentation process. By adding high-titanium slag with a phase of Ti3O5 as a titanium-containing raw material to the taphole mud, TiC, TiN or Ti(C,N) are more easily generated under the action of nitrogen and carbon. Since the wetting angle of molten iron and slag to these titanium compounds is small, some iron droplets can easily wet and adhere to the thin shell of TiC, TiN or Ti(C,N). These iron-containing beads will be suspended at the interface of slag and iron due to their low density. In addition, the melting points of TiC (melting point is 3150℃) and TiN (melting point is 2950℃) are much higher than the temperature of slag and iron, so they will not melt completely, but will be suspended in the slag and iron around the iron mouth and at its interface in a semi-molten or solid form.

[0072] During the iron-tapping process, as the slag iron liquid level gradually drops, these small particles containing titanium compounds are squeezed and deposited on the brick lining around the iron mouth and in the brick seams at the bottom of the furnace. At the same time, due to the lower temperature and rough surface of the brick lining near the furnace wall, the eroded brick lining is more conducive to the precipitation of low-valent titanium compound crystals. After adding titanium-containing materials to the taphole mud, these low-valent titanium compounds can be continuously precipitated in the iron mouth area, and as the edge of the mud bag changes, a titanium layer is gradually formed on the surface of the brick lining. This titanium layer has a dense structure, high hardness, excellent heat resistance and a high melting point (the melting end temperature can reach 1500℃). This high-melting-point adhesive adheres to the furnace hearth and furnace bottom brick lining around the iron mouth, which effectively protects these parts, slows down the erosion of the iron mouth, furnace hearth and furnace bottom, and thus prolongs the service life of the blast furnace.

[0073] The present invention adopts carbon black with high carbon content and small particle size as the carbon source. Carbon black has the advantages of low thermal expansion coefficient, large specific surface area, high surface activity and high thermal conductivity. First, due to its large specific surface area and good adsorption performance, carbon black significantly increases the contact area between carbon and high titanium slag in the taphole mud, which makes it easier for carbon and high titanium slag to undergo reduction reaction and generate TiC. Secondly, the structure of carbon black makes it easier to disperse evenly in various media, which helps to improve the overall uniformity and stability of the taphole mud. Through the uniform dispersion characteristics of carbon black, the present invention not only enhances the integrity of the taphole mud, but also improves its anti-corrosion performance, ensuring that the taphole mud is more stable and durable in the blast furnace, thereby improving the protection effect of the iron mouth area.

[0074] Metal aluminum has two significant effects as a catalyst. First, metal aluminum can effectively reduce the activation energy of the reaction between titanium oxide and carbon and nitrogen, thereby accelerating the reaction process. This allows a large amount of highly refractory TiC, TiN and Ti(C,N) solid solutions to be generated near the iron mouth of the blast furnace in a relatively short period of time. The rapid generation of these refractory materials significantly enhances the high temperature resistance and wear resistance of the iron mouth and its surrounding areas. Secondly, under high temperature conditions, the taphole mud will release a large amount of water vapor, and the metal aluminum reacts with the water vapor to generate hydrogen and aluminum hydroxide. The reaction equation is:

[0075] 2Al+6H2O→2Al(OH)3+3H2+954J

[0076] The hydrogen generated in this reaction process plays a dual role: first, hydrogen directly participates in the reduction reaction of high-titanium slag, improves the reduction efficiency, and promotes the further generation of TiC and TiN; second, hydrogen forms a tiny pore structure in the iron mouth channel. These microporous structures can effectively alleviate the crack stress generated by the channel under high temperature and mechanical stress, reducing the risk of iron mouth fracture and leakage. Such microporous structures not only improve the stability of the iron mouth, but also enhance its durability, thereby further extending the service life of the blast furnace.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An in-situ synthesized functional titanium taphole mud for blast furnace, characterized in that: In terms of weight, the proportions of each component are as follows: 8-15 parts of the first bauxite, 8-15 parts of the second bauxite, 8-15 parts of the first silicon carbide, 7-15 parts of 1-0mm kyanite, 8-15 parts of ferrosilicon nitride, 10-20 parts of the second silicon carbide, 3-8 parts of Guangxi mud, 5-15 parts of titanium-containing raw materials, 1-3 parts of carbon sources, 1-3 parts of catalysts, 1-3 parts of metallic silicon powder, 1-7 parts of nitrogen sources and 10 parts of binders.

2. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 1, characterized in that: In terms of weight, the proportions of each component are as follows: 10 parts of the first bauxite, 15 parts of the second bauxite, 10 parts of the first silicon carbide, 10 parts of 1-0mm kyanite, 10 parts of ferrosilicon nitride, 10 parts of the second silicon carbide, 5 parts of Guangxi mud, 10 parts of titanium-containing raw materials, 2 parts of carbon sources, 1 part of catalysts, 2 parts of metallic silicon powder, 5 parts of nitrogen sources and 10 parts of binders.

3. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 1, characterized in that: The ferrosilicon nitride is 200 mesh ferrosilicon nitride; the second silicon carbide is 325 mesh silicon carbide.

4. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 1, characterized in that: The Guangxi mud is 200 mesh Guangxi mud.

5. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 1, characterized in that: The titanium-containing raw material is 200-mesh high-titanium slag.

6. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 5, characterized in that: The physical phase of the 200-mesh high-titanium slag is Ti3O5, and the titanium oxide content is ≥80%.

7. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 1, characterized in that: The carbon source is carbon black with fixed carbon content ≥98%, ash content ≤16%, S ≤1.0%, moisture content ≤1.0% and a particle size of 325 meshes.

8. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 1, characterized in that: The catalyst is 325 mesh aluminum powder.

9. The in-situ synthesized functional titanium taphole mud for blast furnace according to claim 1, characterized in that: The nitrogen source is selected from one of 200 mesh ammonium sulfate or 200 mesh ammonium dichromate.

10. A method for preparing functional titanium taphole mud for blast furnace according to any one of claims 1 to 9, characterized in that: Here are the steps: Step 1: According to the proportion, ferrosilicon nitride, first silicon carbide, Guangxi mud, high titanium slag, carbon black, metal aluminum powder, metal silicon powder, ammonium sulfate or ammonium dichromate are uniformly premixed in a premixing tank for 30 minutes and set aside; Step 2: Add alumina, second silicon carbide, kyanite and part of the binder into a mixer at 70-80°C according to the proportion, and mix for 5 minutes; then, add the fine powder premixed in step 1 into the mixer, and mix for another 5 minutes; then, add the remaining binder, and continue mixing for 50 minutes until it is evenly mixed, and press the mixture into shape to obtain titanium cannon mud.

Citation Information

Patent Citations

  • Anhydrous stemming and preparation method thereof

    CN106986657A

  • Anti-corrosion and low-consumption type anhydrous stemming for large-scale blast furnace taphole

    CN108658588A

  • Carbon composite anhydrous stemming for large blast furnace and preparation method thereof

    CN110981447A

  • Tap hole area carbon brick temperature reduction method

    CN111826489A

  • Environment-friendly high-strength anhydrous stemming and preparation method thereof

    CN113149623A

Cited By

  • Titanium-containing anhydrous stemming for blast furnace and preparation method of titanium-containing anhydrous stemming

    CN120903954A